Pitiríase versicolor, dermatite seborreica, xerodermia e prurido em mulheres grávidas ou não grávidas, infectadas ou não infectadas pelo HIV - Claudemir Roberto Aguilar (2012)
Introduction: there are few data available about pityriasis versicolor (PV) in pregnant women and/or infected by human immunodeficiency virus (HIV) and the cutaneous manifestations related to HIV are based predominantly in men. Objectives: to estimate prevalence and variables associated whit PV, seborrheic dermatitis (DS), xerosis (XE) and pruritus (PR) in 816 women: pregnant or nonpregnant and infected or uninfected with HIV. Methods: cross-sectional study including patients of public services in the city of Belo Horizonte, Brazil, examined by dermatologists from July 2008 to April 2011. The dermatoses were diagnosed based on their clinical findings, and the PV was confirmed by mycological examination. There were evaluated several variables of interest for each of these diseases, such as sociodemographic and behavior characteristics, the use of antiretroviral (ARV) and the markers of HIV progression. For the statistical analysis there were used the Kruskal-Wallis test to check the homogeneity between the groups, the X2 test and Fisher's Exact test, for evaluating the qualitative effect of the predictors, and the Mann-Whitney test for verifying quantitative predictors. The multivariate analysis was performed by logistic regression, keeping only the significant variables in the final model (p <0.05). Results: the prevalence of PV was 4.9%, increasing your chance of four times when the family history of PV (HFPV) was positive, in 10 times when there was previous history for PV (HPPV) and decrease your chance in 0.9 times for each year increase in age. DS prevalence was 3.6%, with three times more chance to occur in patients with oily skin, two more chance in HIV-infected women and, in these women, 2.8 more chance when viral load was greater than or equal to 400 copies/mL. The prevalence of XE was 18.4%, with a increasing chance of 20 times in pregnant women, 250 times in those HIV-infected and, in these women, at 5.7 times when they were using ARV. PR prevalence was 15.6%, with a greater chance of 18 times in the pregnant women, seven times in XE and two times in atopic. Conclusions: the pregnancy was significantly associated with XE and PR, but not with PV and DS. HIV infection was significantly associated with DS and XE, but not with PV and PR. HFPV and HPPV positive were associated with a greater chance of PV, while advancing age associated with a lower chance. High chance of PR was still associated with the presence of XE and atopy.